"Everyone Working a Little More Closely Together": The Transnationalization of Creative Production in TV Production Conglomerates. (November 2020) - van Keulen, Jolien; Bauwens, Joke; Krijnen, Tonny
To survive contemporary developments in the TV industry and as a result of international mergers and acquisitions, production companies often form transnational media corporations. In this article, we examine TV production groups as global-local networks that pursue competitive advantages of transnational integration. Combining a critical industry studies approach with management perspectives, and building on different data sources, this article aims to open up the black box of management beliefs, discourses, and material practices within TV production networks. Our analysis shows how the industry's hunt for profitable, reproducible practices and intellectual property (IP) rights translates into transnational creative pipelines, knowledge flows, and interdependencies. Transnational management practices include surveillance of local production, the installation of information flows, shared practices and procedures, and socialization processes. This article argues that corporate structures, strategies, and management practices coordinate TV production across borders, shape industrial practices, and foster a transnational production culture.